Interactions between rearward-facing child restraint systems and the front row seatback in frontal impact sled tests. (10th October 2022) - Patton, D. A.; Maheshwari, J.; Arbogast, K. B.
Abstract: Objective: Some child restraint system (CRS) manufacturers specify a minimum distance between the CRS and the seatback, whereas others require that the CRS may contact the seatback but cannot be "braced"; however, few studies have investigated these interactions. Therefore, the aim was to investigate the interactions between the front row seat and rearward-facing CRS models with and without a support leg during frontal crashes. Methods: Sled tests using the FMVSS 213 frontal crash pulse were performed with the Q1.5 and Q3 anthropomorphic test devices (ATDs) seated in rearward-facing infant and convertible CRS models, respectively. A front row vehicle seat was in front of the test bench in three track positions: brace, touch and gap. For the touch condition, the front row seat was translated aftward until the seatback contacted the CRS. For the brace condition, the front row seat was translated 20 mm aftward. For the gap condition, the front row seat was translated 50 mm forward. Each condition was tested with and without the support leg of the CRS. Results: The tests with a support leg were associated with significantly (p = 0.007) lower resultant linear head acceleration 3 ms clip compared to the tests without a support leg, but the reduction of head injury criterion 15 ms (HIC15) was not significant (p = 0.057). The Q1.5 ATD in the rearward-facing infant CRS with a support leg had the lowest injury metrics for the touch and gap conditions, whereas the Q3 in the rearward-facing convertible CRS had the lowest head injury metrics for the brace condition. Conclusions: The use of a support leg provided a clear benefit in terms of reducing head injury metrics for the Q1.5 in the rearward-facing infant CRS, especially for the touch and gap conditions. The rearward-facing convertible CRS in the current study appears to benefit from being braced against the front row seat. However, further tests are required to allow further statistical comparisons and determine if these preliminary findings extend to other rearward-facing CRS models.